Building theory in public relations: Interorganizational relationships as a public relations paradigm. Issue 4 (4th July 2018) - Ferguson, Mary Ann
ABSTRACT: This article suggests that agreement on a paradigm focus for public relations scholarship would greatly enhance the probability of productive theory development. The author argues, influenced by Thomas Kuhn, that until those who call themselves public relations scholars come to agreement on the focus of public relations research and theory development, there may be much activity we call research in public relations, but there will not be much theory development.